2013
DOI: 10.1080/00380768.2013.809599
|View full text |Cite
|
Sign up to set email alerts
|

Amendment of hydroponic nutrient solution with humic acid and glutamic acid in tomato (Lycopersicon esculentumMill.) culture

Abstract: Can humic acid (HA) and glutamic acid (GA), when added to tomato (Lycopersicon esculentum Mill. cv. 'Hongyangli') nutrient solution in a hydroponic system, improve growth? Tomato seedlings were grown in six nutrient solutions: (1) control (C), (2) C + 25 mg L -1 HA (HA1); (3) C + 50 mg L -1 HA (HA2); (4) C + 100 mg L -1 GA; (5) HA1 + GA; (6) HA2 + GA. Various biochemical and physiological parameters were measured. HA increased photosynthesis rate and mesophyll conductance. HA did not significantly affect trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…A three-year investigation by Suman and collaborators [209] found that adding 0.5 L humic acid ha −1 via fertigation to open-field-grown tomato plants did not enhance growth and yield when fertilization was 100% of the recommended dosage, which is also consistent with what Monda and collaborators [211] recently found. When fertilization was 80% of the recommended dosage, it performed significantly better than its untreated control (12.6% higher yielding), and statistically equal to the 100% fertilization group; the same results were also recorded when 25 and 50 mg of HAs were added to a full-strength nutrient solution [212], which may point to differences in either the plant, the experimental setup, and/or the HA source material and dosage.…”
Section: Implication Of Biostimulant Substance Treatments On Nightshade Green Growth and Fruit Yieldmentioning
confidence: 69%
“…A three-year investigation by Suman and collaborators [209] found that adding 0.5 L humic acid ha −1 via fertigation to open-field-grown tomato plants did not enhance growth and yield when fertilization was 100% of the recommended dosage, which is also consistent with what Monda and collaborators [211] recently found. When fertilization was 80% of the recommended dosage, it performed significantly better than its untreated control (12.6% higher yielding), and statistically equal to the 100% fertilization group; the same results were also recorded when 25 and 50 mg of HAs were added to a full-strength nutrient solution [212], which may point to differences in either the plant, the experimental setup, and/or the HA source material and dosage.…”
Section: Implication Of Biostimulant Substance Treatments On Nightshade Green Growth and Fruit Yieldmentioning
confidence: 69%
“…In our study, fulvic acids increased the concentrations of minerals and carbon-containing substances related to product quality in the edible portion of vegetables (Table 7, Supplementary Table 1, Figure 2, and Supplementary Figure 6). Several studies confirm an improvement of vegetable quality by humic-like substance application (Haghighi and Teixeira Da Silva, 2013).…”
Section: Fulvic Acids Increased the Quality Of Vegetablesmentioning
confidence: 84%
“…Indeed, it is well documented that application of glutamic acid improves plant development (Sun and Hong, 2010), especially by enhancing N metabolism (Haghighi, 2012). Glutamic acid could improve photosynthesis due to a better chlorophyll content and velocity of Rubisco; it also induces the activities of nitrate reductase and glutamine synthase, leading to a higher soluble protein content, leaf N content, and N accumulation in leaves (Yu et al, 2010;Haghighi and Silva, 2013). In addition, glutamic acid alleviates abiotic stress, such as cold during the early vegetative stage in rice (Jia et al, 2017).…”
Section: Organic Acids Enhanced the Effect Of Glutamic Acid In Wheat mentioning
confidence: 99%